Risk factors associated to mortality by novel Influenza A (H1N1) in Cusco-Peru - Grajeda Annca, Pablo F. (2013)
Introduction: 395 confirmed cases of new influenza A (H1N1) cases and 15 deaths were reported in the Cusco Region during 2009. The case fatality rate of 3.8%, was well above national and international reports, becoming serious public health problem. Objective: To determine the risk factors associated with mortality novel influenza A (H1N1). Material and methods: a study of cases and controls was conducted in 3 hospitals in the city of Cusco, between Epidemiological Weeks 18-34, 2009. 15 confirmed cases and 45 controls were identified PCRtr. Considering "case" all confirmed case of novel influenza A (H1N1) hospitalized and died and "control" means a confirmed case of novel influenza A (H1N1) hospitalized and discharged alive. Results: Of 24 risk factors associated with mortality from New influenza A (H1N1) studied, the following were identified: start time greater antiviral treatment of 3 days (p = 0.001), while higher corticosteroid therapy 5 days (p = 0.00001), time (p = 0.0003) increased hospitalization of 7 days (p = 0.0003), time of antibiotic therapy greater than 10 days (p = 0.0001), time measures more support 10 days (p = 0.001) , moderate to severe commitment consciousness as APACHE II Score (p = 0.0000000), hypertension (p = 0.001), anemia (p = 0.01), hypokalemia (p = 0.01), hypoxia (p = 0.0005) and leukocytosis (p = 0.01). The logistic regression analysis showed that a subject included in the study more than 10 days antibiotic therapy (p <0.007), while higher corticosteroid therapy 5 days (p <0.05) and initiation of antiviral treatment more than 3 days (p <0.05) had high probability of death of 84%. Conclusions: The most important risk factors for mortality novel influenza A (H1N1) were identified: Home antiviral treatment more than 3 days, more time corticosteroid therapy 5 days and more 10 days antibiotic therapy, having communicated the results of research to health workers, improving early identification of these risk factors and intervene on them or try to avoid them and improve the quality of care processes of patients was observed, not having submitted any other death in 2009.